MORPHOLOGICAL GROUND OF NECESSITY TO SUTURE TOGETHER VAGAL TRUNKS - Kunitsa V. N.,; Barsukov, N.P.; Pikalyuk V. S.,; Novoselskaya, N.А.; Yarovaya, О.Y. (World of Medicine and Biology, 2013)
35 mongrels were opareted by left side thoracotomy. Both vagal trunks is separateed from surrounding tissues, a nerve intersected between ligatures. The preservatived hollow tube from spinal root of the beef cattle was put on the pereferal pat of a nerve. The end of nerves were compared with two provisory epineurial sutures. It was done with atraumatic needle. The end of experement was according to a ruls of biological ethics (3, 7, 14, 30, 60, 90, 180 days). Histological, histochemistry, neuromorphological research of place when the end of nerves were connected was conducted. Even the initial step of experiment had first signs of regeneration of the vagus nervs. In a month after neuroraffia a regenerating nerve fibers has ingrowed through a scar. In 180 days the distal end of nerve is fully filled by regenerating axons. Loose nature of scar assists the intensive germination of fibres through him, and late terms does not result in development of secondary degenerative changes.
Keywords: vagal trunks; regeneration; neuroraffia